Pembentukan Kapsul/Nodul Larva Helicoverpa armigera Hubner (Lepidoptera : Noctuidae) Pasca Infeksi HaNPV (Helicoverpa armigera NUCLEAR POLYHEDROSIS VIRUS) - Nani, Kurnia (bionature, 2010)
NPV is one of the biological insecticides that kills the target by infecting their cells including hemocytes. Hemocytes play a key role on defence mechanism against pathogens like NPV. This defense mechanism may cause the insect to become more tolerant as well as to chemical insectisides. The tolerances of insect to NPV could be induced by cellular immune system (CIS). One of the CIS is capsules/nodules formation. Based on that assumption, this research was conducted to observe the alteration of capsules/nodules formation of Helicoverpa armigera larvae post sublethal infection of HaNPV (Helicoverpa armigera nuclear polyhedrosis viruses). The fifth instar Helicoverpa armigera ware infected by sublethal doses of HaNPV. 24 hour post infection, partly of survive larvae reared to get their first (NPV-F1) and second filial (NPV-F2). Another survivor induced by hit killed Bacillus cereus, and then its haemocoel were exposed under stereo microscope (total magnification, 60 X) to watch capsules/nodules that appear as black spots on haemolymph. This procedure also conducted to fifth instar larvae of NPV-F1, NPV-F2, control (K-P) and their filial (K-F1 and K-F2), blank and placebo. The result showed that the number of nodules/capsules on larvae were not significant between control and the NPV-treat larvae on every generation, which was about 4 nodules/capsules. It showed that there is no cellular immune respon changed on NPV-P larvae, so their immune ability are similar to larvae K-P. The recoveries of NPV-P larvae cause it have a good capability to produce offspring with good immune response. So, NPV-F1 and NPV-F2 larvae have same ability as K-F1 and K-F2 larvae. It can be concluded that the use of sublethal dosage of HaNPV has not changed formation of capsules/nodules of H. armigera larvae and their offspring.